2014
DOI: 10.5935/1676-4285.20144744
|View full text |Cite
|
Sign up to set email alerts
|

Initial care to burn victims: nursing students' knowledge: a cross-sectional study

Abstract: Problem: The scientific literature has been pointing out gaps in the knowledge of nurses on the care of burn victims. Aim: To determine the theoretical knowledge of nursing students on the initial care to burn victims in emergency units. Method: Cross-sectional study involving 107 nursing students from four higher education institutions in the Metropolitan Area of Maringá (PR), using a semi-structured questionnaire for data collection. Association was evaluated using the chi-square test, with significance leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…The study confirms the results of studies by some researchers (Заякова et al, 2014), (Каишева et al, 2018), (Jordan & Harrington, 1997), (Kohn, 2000), (Meschial & Oliveira, 2014) that the practical training of nurses in terms of medical care for burns is significantly insufficient. A self-assessment of the respondents found that 26.49% had some practical training for burn care, 20.56% were those who could not judge and those who said no were 17.18%.…”
Section: Discussionsupporting
confidence: 89%
“…The study confirms the results of studies by some researchers (Заякова et al, 2014), (Каишева et al, 2018), (Jordan & Harrington, 1997), (Kohn, 2000), (Meschial & Oliveira, 2014) that the practical training of nurses in terms of medical care for burns is significantly insufficient. A self-assessment of the respondents found that 26.49% had some practical training for burn care, 20.56% were those who could not judge and those who said no were 17.18%.…”
Section: Discussionsupporting
confidence: 89%
“…7 From this perspective, the academic training of students must focus on the development of clinical reasoning, and on the skills needed to treat the burn victim, including content that emphasizes primary care. 8 However, studies in the literature show that nursing students present unsatisfactory knowledge and inadequate education regarding the initial treatment of burn patients. 8,9 Curriculum analysis of the nursing course in a metropolitan area of Brazil showed mainly need for adapt and structuring of theoretical and practical content of teaching in this area.…”
Section: Introductionmentioning
confidence: 99%
“…8 However, studies in the literature show that nursing students present unsatisfactory knowledge and inadequate education regarding the initial treatment of burn patients. 8,9 Curriculum analysis of the nursing course in a metropolitan area of Brazil showed mainly need for adapt and structuring of theoretical and practical content of teaching in this area. 10 To fill these gaps, nursing education should focus on the development of practical and interpersonal skills aimed at better decision-making and problem solving in all health and disease situations.…”
Section: Introductionmentioning
confidence: 99%
“…A study carried out in England with the objective of evaluating undergraduate students' knowledge on first care measures to burn patients showed that they lack theoretical and practical knowledge (5) . In Brazil, few investigations to date have evaluated the knowledge and training of nursing professionals to provide care for burn victims (6) .…”
Section: Introductionmentioning
confidence: 99%